Bacterial leaching of nickel literites using chemolithotrophic microorganisms - Simate, Geoffrey Simate (My University, 2009)
Biohydrometallurgy, an interdisciplinary field involving geomicrobiology, microbial ecology, microbial biochemistry, and hydrometallurgy, is a promising novel technology for recovering valuable minerals from traditionally difficult-to-process ores. In this study, the possibility to treat nickel laterites biohydrometallurgically using chemolithotrophic microorganisms was investigated. Nickel laterite contains metal values but is not capable of participating in the primary chemolithotrophic bacterial oxidation because it contains neither ferrous iron nor substantial amount of reduced sulphur. Its metal value can, however, be recovered by allowing the primary oxidation of pyrite, or similar iron/sulphur minerals to provide sulphuric acid solutions, which solubilise the metal content. In order to have an insight on the use of chemolithotrophic bacteria in this process, it was important to first understand the role and effects of sulphuric acid. Its effect was compared to citric acid and ferric sulphate. Results showed that sulphuric acid performed better, in terms of nickel recovery, than citric acid or ferric sulphate of the same initial concentration. However, citric acid performed better at the same initial pH. A synergic effect was observed in a mixture of sulphuric and citric acids. In the bacterial leaching test works, sulphur substrate exhibited better effects in terms of acidification and nickel recovery than pyrite substrate. Using a statistically-based optimization strategy called response surface methodology, the theoretical optimum conditions for maximum nickel recovery (79.8%) within the range of conditions studied was found to be initial pH of 2.0, 63μm particle size and 2.6% pulp density. This work has shown that by the addition of a sulphur containing material, nickel laterites can be leached by chemolithotrophic microorganisms via the sulphuric acid produced.